Monitorování úspěšnosti transfekce buněčné linie 293 HEK - Dvořák, Tomáš (Vysoké učení technické v Brně. Fakulta chemická, 2011)
Diplomová práce je založena na monitorování úspěšnosti transfekce buněčné linie 293HEK. V teoretické části je popsán princip transfekčních metod, buněčné linie, vektory a reportérové geny. V praktické části byly použity buňky HEK293 EBNA1. Byl zkoumán rozdíl mezi plasmidy GFP a EGFP. Dále byly použity různé transfekční regenty za různých kultivačních podmínek.

Diploma thesis is based on monitoring the succes of transfection of cell linie HEK293. In theoretical part are described principles of transfection methods, cell lines, vectors and reporter genes. HEK293 cells EBNA1 were used for practical part. It was studied the difference between GFP and EGFP plasmids. As well as using various transfection reagents under different culture conditions.
Monitoring the success of transfection of cell line 293 HEK
Keywords: transfekce; GFP; HEK293 EBNA1; r-protein; vektory; reportérové geny; transfection; GFP; HEK293 EBNA1; r-protein; vectors; reporter genes